PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, LIKUIDITAS, PERTUMBUHAN PENJUALAN, RISIKO BISNIS DAN STRUKTUR AKTIVA TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR PERIODE 2012-2016 - Anik Rahmatika, 14.05.52.0244; Puspitasari, Elen (Students' Journal of Accounting and Banking, 2018)
This study examines and analyzes the effect of Profitability, Company Size, Liquidity, Sales Growth, Business Risk and Asset Structure on Capital Structure, in the 2012-2016 Manufacturing companies listed on the Indonesia Stock Exchange. The population in this study in manufacturing companies listed on the Indonesia Stock Exchange in the period 2012 to 2016. The selection of samples using purposive sampling with the study period of 2014 to 2016 obtained observation data as much as 388. The data used is secondary obtained from financial statements in manufacturing companies on the Indonesian Stock Exchange (IDX). Analysis of the influence between variables using multiple linear regression analysis method. The results of this study indicate that: Profitability, Liquidity, Business Risk have a negative effect on Capital Structure, While Company Size, Sales Growth and Asset Structure have a positive effect on Capital Structure. Keywords: Profitability, Company Size, Liquidity, Sales Growth, Business Risk and Asset Structure